2018
DOI: 10.1002/chem.201801044
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Speciation and Supramolecular Assembly in the 5f Block

Abstract: Hybrid materials bearing elements from the 5f block display a rich diversity of coordination geometries, connectivities, and assembly motifs. Exemplary in this regard have been uranyl coordination polymers, which feature a wide range of secondary building units resulting from hydrolysis and oligomerization of the [UO ] cation. An alternative approach to novel materials, however, suppresses hydrolysis and relies on non-covalent interactions (e.g. hydrogen or halogen bonding) to direct assembly of a more limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…As the use of actinides in both the nuclear power and defense sectors over the past 70 years has resulted in environmental releases of radionuclides generated during associated activities, the development of aqueous actinide chelation chemistry remains continuously relevant. , Understanding the fundamental bonding interactions of individual actinide cations is critical for ongoing efforts focused on improving actinide decorporation therapies and developing new environmental remediation strategies. This is particularly true for the highly water-soluble uranyl cation, U VI O 2 2+ , which is the predominant form of uranium (U) found in the environment. , The significant mobility of the uranyl cation introduces risks for radiological contamination, which is a crucial public health issue, as uranium exhibits both chemical and radiological toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…As the use of actinides in both the nuclear power and defense sectors over the past 70 years has resulted in environmental releases of radionuclides generated during associated activities, the development of aqueous actinide chelation chemistry remains continuously relevant. , Understanding the fundamental bonding interactions of individual actinide cations is critical for ongoing efforts focused on improving actinide decorporation therapies and developing new environmental remediation strategies. This is particularly true for the highly water-soluble uranyl cation, U VI O 2 2+ , which is the predominant form of uranium (U) found in the environment. , The significant mobility of the uranyl cation introduces risks for radiological contamination, which is a crucial public health issue, as uranium exhibits both chemical and radiological toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…These interactions and the utilization thereof rely on structure-directing attractive forces detailed within a hierarchy of acceptor–donor pairing preferences to explore substantive influences on the packing of molecular species in the solid state and their properties . Efforts to explore and categorize NCIs have historically been focused on hydrogen bonding and π-stacking motifs in organic molecules, and have evolved more recently to include assembly trends in transition metal containing hybrid materials , and the utilization of other, more diverse NCIs, such as halogen or pseudohalogen bonding. In our group, we have focused primarily on halogenated organic ligands to assemble lanthanide- and actinide-containing , materials through a variety of noncovalent interactions to establish trends therein with attention toward predictive noncovalent assembly.…”
Section: Introductionmentioning
confidence: 99%
“…However, uranium wastewater is generated during mining and using process, which can cause certain pollution to the environment. [7][8] Among uranyl functional complexes, the main valence of uranium is IV and VI, [9][10][11][12] and the recovery and reuse of uranium have always been an urgent research topic for researchers. [13][14] The structural diversity of uranyl functional complex materials is very variously [,15] three common spatial configurations are quadrangular bipyramid, pentagonal bipyramid and hexagonal bipyramid respectively.. [16][17][18][19][20][21][22][23] Through recent researches, we have found that uranyl ions are easier to coordinate with carboxyl and amino groups to form complexes, and ligands with multiple coordination sites are easier to form a network structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, uranium wastewater is generated during mining and using process, which can cause certain pollution to the environment [7–8] . Among uranyl functional complexes, the main valence of uranium is IV and VI, [9–12] and the recovery and reuse of uranium have always been an urgent research topic for researchers [13–14] . The structural diversity of uranyl functional complex materials is very variously [,15] three common spatial configurations are quadrangular bipyramid, pentagonal bipyramid and hexagonal bipyramid respectively.…”
Section: Introductionmentioning
confidence: 99%